High performance polyethersulfone/TiO2-AgBr-Ag photocatalytic membrane for Cefixime removal from water under visible light - Shahnaz Nayeri; Jalal Basiri Parsa (Desalination and Water Treatment, 2024)
PES/TiO2-AgBr-Ag membrane with different loadings of TiO2-AgBr-Ag was investigated as a photocatalyst for the remove of Cefixime (CFX) in aqueous solution to solve the separation problems of the suspended photocatalysts and membrane fouling that happen in photocatalytic technology. The prepared membranes underwent characterization using various analytical techniques including XRD, FE-SEM, AFM, DRS, FT-IR, EDX and CA methods. The Cross-sectional images of SEM also show that the prepared membranes transformed into porous structures with finger-like porosity, and the porosity of pure PES increased up to 1.5 wt% PES/TiO2-AgBr-Ag then decreases slightly due to the onset of aggregation. The EDX analysis revealed a uniform dispersion of the nanoparticles in the PES membrane matrix. The contact angle of the membranes was observed to decrease from 77° to 30° upon the augmentation of TiO2-AgBr-Ag content. However, increasing the TiO2-AgBr-Ag loading to 2 wt% results in a decrease in performance, which is due to agglomeration and a possible defective porous structure of the membrane. Furthermore, the mentioned blended membrane showed a higher flux recovery rate (FRR (%)) in the Cefixime fouling.